Effect of Flow Rate Scaling on SAE-InAs Crystal Phase and Integration of Self-Catalyzed InAs/InSb Heterostructure Nanowires on Si (111) Substrate by MOCVD. (19th July 2021) - Anandan, Deepak; Yu, Hung Wei; Lee, Ching Ting; Dee, Chang Fu; Hamzah, Azrul Azlan; Chang, Edward Yi
Abstract : The effect of III-V molar flow scaling on crystal quality of selectively grown InAs nanowires on patterned Si (111) substrate is investigated by metal organic chemical vapor deposition. We found the correlations between molar flow rate scaling and selectivity and InAs crystal structure have been investigated. When the molar flow rate is higher, nanowire follows random nucleation and exhibits zincblende crystal structure, whereas growth selectivity increases to 97% at intermediate molar flow rates and nanowire exhibits wurtzite dominant crystal phase with occasional stacking faults. Once the molar flow rate is scaled-down aggressively, nanowire exhibits polytype crystal structure with small degradation in selectivity. The resistivity calculated from current-voltage curve of moderate molar flow rate InAs nanowires showed 15.9 × 10 –3 Ωcm, which was significantly (1.6 times) lower than typical InAs nanowires with low molar flow rate (25.31 × 10 –3 Ωcm). Finally, we integrate axial InSb heterostructure nanowire with two different crystal structures on InAs stem by self-catalyzed selective area epitaxy for the V/III ratio of 2. This study further offers good opportunity to tune the crystal structure of InSb with the help of In-catalyzed growth technique.